Children’s Dances at First Nation Powwows in Atlantic Canada: A Preliminary Inquiry - Tulk, Janice (Ethnologies, 2015)
In this article, based on ethnographic research conducted at Mi’kmaw powwows throughout Atlantic Canada between 2004 and 2010, I will begin to address the lacuna in literature on First Nation children’s dances. I will describe the various children’s dances observed at powwows in Eastern Canada, as well as songs that are specifically used for children’s dances, contextualizing them within the traditional powwow event and in relation to emcee stage talk. I will also illuminate the socio-cultural functions of children’s dance at powwows and the relationship between dance and play. Finally, by focussing specifically on the living dance tradition of Mi’kmaq at cultural events in the Atlantic provinces, I will elucidate some of the forces that act upon informal culture, shaping and re-shaping it through time. This approach will highlight the relationship between popular culture and tradition in this context, revealing the emergent nature of lived traditions.